PROPERTIES OF BINDING BITUMINOUS MATERIALS PRODUCED IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the main physical-mechanical and rheological properties of road bitumens and bituminous binders produced in the Republic of Uzbekistan. It examines the local raw material base, production technologies, and their impact on bitumen quality. The article summarizes the results of research on important indicators of bituminous materials such as viscosity, penetration, softening point, ductility, brittleness temperature, and adhesion. Furthermore, the compliance of local bitumens with international standards is evaluated, and their role in ensuring the durability and longevity of road pavements in the climatic conditions of Uzbekistan is substantiated. This article aims to create a scientific basis for the effective use of local bitumen products in road construction, improving their quality, and developing new, modified types of bitumen.